SAFETY OF TEETH EXTRACTIONS IN PATIENTS ON ACENOCOUMAROL THERAPY - Atanaska Dinkova; Hristo Daskalov (Peytchinski Publishing, 2020)
Introduction: Studies evaluating bleeding risk in anticoagulated patients undergoing dental surgical procedures have been conducted for more than 50 years and are still ongoing. The aim of the present study is to clinically evaluate the bleeding after a simple teet extraction in patients on Acenocoumarol (Sintrom) monotherapy, with International Normalised Ratio (INR) below 2,5 at the time of extraction. Material and Methods: In the study were included 60 patients, 44 men and 16 women, taking Sintrom, who underwent 95 simple teeth extractions at the Department of Oral Surgery - Faculty of Dental Medicine, Medical University Plovdiv, Bulgaria. In the study were included patients between 45 - 95 years, divided into Working group (WG) - 30 patients who received oral Acenocoumarol during the treatment; Control group (CG) - 30 patients who discontinued Acenocoumarol 72 hours prior dental treatment. Haemostasis was controlled by local measures: a gelatin sponge and /or wound suturing. Results: In all patients, INR values obtained immediately prior to treatment were sub-therapeutic or therapeutic values up to 2,5. Of all 60 patients, only 4 reported for secondary bleeding (up to 24 and up to 48 hours), which was self-limiting and no additional haemostasis was needed. Conclusion: In patients receiving Acenocoumarol with INR values in the therapeutic range up to 2,5, in the absence of other risk factors, simple tooth extraction can be safely performed without risk of uncontrolled post-extraction bleeding.